Zakat and Islamic Corporate Social Responsibility: Does It Take Effect to the Performance of Shari’a Banking? - Sidik, Ichwan; Reskino, Reskino (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
The less than optimal regulation of zakat companies in sharia banking in Indonesia has been salient to the background of this research. This study aims to examine the influence of zakat and Islamic corporate social responsibility (ICSR) to the reputation and performance of companies. Sample data was selectively gathered from 10 sharia banks in Indonesia from 2011 to 2014. Normality test and logistic regression are used to test the effect of zakat on company reputation, the influence of ICSR on company reputation, the influence of zakat on company performance, and the influence of ICSR on corporate performance. The results show that zakat has a positive influence on and is significant to a company's reputation, that ICSR has a positive influence on and is significant to a company's reputation, that zakat has a positive influence and significant impact on the performance of a company, and that ICSR has a positive relation, but no significant effect on company performance. These findings indicate the importance of paying zakat and ICSR as a business strategy for the sharia banking market in Indonesia today. Keywords: zakat, Islamic corporate social responsibility, company performance